Kamisan Action as a Symbolic Practice of Resistance Against Injustice in West Java - Hifdzi Syahril Mawardi; Ilyas Mulyana; Dadang Kusmana; Muliadi, Muliadi (Penerbit Hellow Pustaka, 2026)
Kamisan Action is a social movement that highlights symbolic resistance against government injustice and impunity. In West Java, this activity emerged as an alternative platform for the public to express political criticism using non-violent symbols such as black clothing, dark umbrellas, and standing still. This study investigates how Thursday Actions in several cities in West Java particularly Bandung function as a symbolic strategy to preserve collective memory of human rights violations and negotiate an increasingly restricted public space. Using a qualitative approach relying on observation and discourse analysis, the research reveals that this silent resistance is able to create new political meanings, strengthen solidarity between victims and advocates, and challenge state narratives that often normalize injustice. Thus, the Thursday Action in West Java not only functions as a memory ritual, but also as a symbolic resistance practice that continuously encourages accountability and social justice. Human rights violations that began since the change of the Old Order to the New Order became the spark for an action to reveal the truth. Starting from the 1965 incident, the mysterious shooting incident of 1982-1985, the enforced disappearances of 1997-1998, the May 1998 tragedy, the Semanggi I tragedy (November 13, 1998), the Semanggi II tragedy (September 24, 1999), the Trisakti tragedy (May 12, 1998), the Munir murder case (September 7, 2004), and many other tragedies are examples of human rights violations whose resolution is still unclear.